E25 Fmri Signal Changes In Frontal Cortex Correlates With Years-to-disease-onset In A Group Of Young Premanifest Huntington Disease Subjects. (17th September 2014) - Nanetti, L; Ferraro, S; Bertolino, N; Piacentini, S; Mandelli, ML; Ghielmetti, F; Castaldo, A; Gellera, C; Nigri, A; Taroni, F; Bruzzone, MG; Di Donato, S; et al.
Abstract : Objective: A functional MRI (fMRI) study to identify and localise the earliest neural changes, in a group of young premanifest Huntington's disease (preHD) individuals, far from estimated clinical onset. Methods: Sixteen preHD, and 18 age/sex matched healthy participants were enrolled. All preHD subjects previously underwent the predictive genetic testing for HD, and did not present neurological signs consistent with HD clinical onset (UHDRS TMS score = 0). Cognitive evaluation of both groups of subjects did not reveal abnormalities. The subjects were submitted to volumetric MRI and fMRI, during the execution of the exogenous covert orienting of attention task. Considering the fMRI task (Posner paradigm) correlation analyses were restricted to the frontal oculomotor cortex identified by the means of a prosaccadic task. In preHD group, multiple regression analysis was performed between fMRI results and the probability to develop the disease onset in the next 5 years (p5HD). Results: fMRI task behavioural performance did not differ between the two groups, while, mean BOLD signal changes of oculomotor frontal cortex was significantly different in the two groups, and, in preHD, correlates with p5HD (r2 = 0.52). A modest correlation (r2 = 0.29) was observed between right putamen volume and p5HD. Conclusion: fMRI activations in the right frontal cortex, correlates with p5HD in a group of preHD individuals very far from onset. This result needs to be confirmed in a larger cohort of preHD subjects enrolled in a longitudinal study, and could represent a possible fMRI biomarker for preHD.